A proposed framework on the relationship between Islamic microfinance related factors and women entrepreneurs business performance in Nigeria - Shehu, Farida Mohammed; Ahmad, Nor Hayati; Al-Aidaros, Al-Hasan (International Foundation for Research & Development, 2015)
Microfinance plays a key role in poverty alleviation, employment generation, mitigating rural urban migration, utilization of local resources and raw materials and contributing to the gross domestic product (GDP) of Nigeria. Women, majority of who are poor and engaged in informal/micro, small and medium scale businesses are mostly the target of microfinance institutions.However, women entrepreneurs find it difficult to have access to the products and services of the conventional banks due to their stringent lending requirement.The presence of Islamic banking which promotes the profit and loss sharing (PLS) concept increases the awareness among women entrepreneurs to alternative funding sources. Despite availability of financing options, women entrepreneurs are constrained by their reluctance to use interest based microfinance services.This paper aims to provide a proposed framework that examines the impact of Islamic investment and financing contracts (Murabaha financing and Mudharabah savings) and other microfinance related factors (training, social capital and self-esteem) on women entrepreneurs business performance.Religiosity is a new moderating variable within the framework that is hypothesized to enhance business performance of women entrepreneurs.The proposed framework will fill the gap in Islamic banking and finance studies since the area of Islamic microfinance and the moderating effect of religiosity has not been empirically investigated.